Oxygen absorbing / desorbing material and exhaust gas purification catalyst

JP2025027415APending Publication Date: 2025-02-27TOYOTA JIDOSHA KK +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023218793
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-14
Filing Date
2023-12-26
Publication Date
2025-02-27

AI Technical Summary

Benefits of technology

【0012】 本発明により、低温作動性及び酸素吸放出能が改善した酸素吸放出材を提供することが可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025027415000001_ABST
    Figure 2025027415000001_ABST
Patent Text Reader

Abstract

To provide an oxygen absorbing / desorbing material having low temperature actuation property and improved oxygen absorbing / desorbing ability.SOLUTION: The invention relates to oxygen absorbing / desorbing material including a Ruddlesden-Popper type laminar perovskite-type composite oxide represented by a formula (0):RE(Fe1-aMa)3Sr3O10-δ(in the formula, RE is at least one or more kinds selected from a group consisting of Pr, Nd, Sm, Eu, Gd, and La; M is at least one or more kinds selected from a group consisting of Mn, Ni, and Co; a is a real number between 0 or more and less than 1; δ is a real number between 0 or more and less than 1) and an exhaust gas purification catalyst using the oxygen absorbing / desorbing material.SELECTED DRAWING: Figure 1A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an oxygen absorbing / releasing material and an exhaust gas purifying catalyst using the oxygen absorbing / releasing material. [Background technology]

[0002] With the progress of motorization on a global scale, the number of automobiles sold is on the rise, and from the perspective of protecting the global environment, there is a demand for high performance catalysts for purifying automobile exhaust gases. Three-way catalysts, which are the mainstream catalysts for gasoline engines, use a feedback control system consisting of an air-fuel ratio sensor and an electronic fuel injection device to reduce nitrogen oxides (NO x These are purified by using an air-fuel ratio that produces chemically equivalent amounts of oxidants such as CO and unburned hydrocarbons (HCs), and reducing agents such as carbon monoxide (CO) and unburned hydrocarbons (HCs). However, in an environment where the exhaust gas composition fluctuates drastically depending on the driving conditions, this purification ability cannot be fully demonstrated.

[0003] The oxygen absorbing / releasing material contained in the three-way catalyst absorbs and releases oxygen through a redox reaction of cations in the solid when the air-fuel ratio fluctuates, and adjusts the oxidizing agent and reducing agent to a stoichiometric ratio that allows the catalyst to function. Ceria (CeO2) has traditionally been used as a material with such oxygen absorption / release capacity (also called oxygen absorption capacity or oxygen storage capacity), and in recent years, various types of composite oxides containing ceria have been researched, with ceria-zirconia (CeO2-ZrO2) composite oxides being particularly widely used. However, the oxygen absorption / release capacity of ceria-zirconia composite oxides is approaching its theoretical limit.

[0004] As a cationic species that can exceed the limit of the cerium ion in the ceria-zirconia composite oxide, there are first transition metal ions with smaller atomic weights than the cerium ion, and various transition metal composite oxides have been developed. For example, Patent Document 1 discloses an oxygen storage material made of a composite oxide containing ferric oxide (Fe2O3), zirconia (ZrO2), and rare earth element oxide, but the oxygen absorption and release capacity of these iron-based oxygen absorption and release materials is not necessarily sufficient.

[0005] The difference in performance between oxygen storage and release materials made of ceria-zirconia composite oxide and iron-based oxygen storage and release materials is believed to be due to the difference in the chemical properties of iron ions and cerium ions. Specifically, the one-electron reaction (Fe 3+ +e - =Fe 2+ ) is 0.771 V, and the standard electrode potential at cerium ion (Ce 4+ ), which is lower than the equivalent potential of 1.71 V, indicates that it is difficult to chemically reduce. In addition, the reaction from divalent iron ions contained in ferrous oxide to zero-valent metal (Fe 2+ +2e - =Fe 0 ) is -0.44V, while the potential at the trivalent cerium ion (Ce 3+ ) to a zero-valent metal (Ce 3+ +3e - =Ce 0 ) is -2.34V, so Fe 2+ Ce 3+ Due to these differences in chemical properties, ferric oxide generally has a higher operating temperature than cerium oxide in terms of oxygen absorption / release capacity, and in a reducing atmosphere, the oxide structure collapses due to reduction to a zero-valent metal, and improving these properties was one of the major challenges in investigating iron-based oxygen absorption / release materials.

[0006] In view of this issue, iron-based composite oxides capable of redox reactions (topotactic transitions) without structural collapse in a high-temperature reducing atmosphere have been developed. For example, Non-Patent Document 1 describes a strontium-iron-based composite oxide, Sr3Fe2O, which exhibits excellent oxygen absorption / release capacity and high reduction resistance. 7-δ However, Sr3Fe2O 7-δ However, the operating temperature for the oxygen absorption / release capacity was high, and there was room for further improvement in the oxygen absorption / release capacity. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2013-241328 A [Non-patent literature]

[0008] [Non-Patent Document 1] Journal of Materials Chemistry A, 2015, 3, 13540-13545 Summary of the Invention [Problem to be solved by the invention]

[0009] As described above, conventional iron-based oxygen absorbing / releasing materials are required to have further improvements in low-temperature operability and oxygen absorbing / releasing capacity. Therefore, an object of the present invention is to provide an oxygen absorbing / releasing material having improved low-temperature operability and oxygen absorbing / releasing capacity. [Means for solving the problem]

[0010] The present inventors have discovered that a Rudolfsden-Popper type layered perovskite complex oxide having a specified composition has excellent low-temperature operation properties and high oxygen absorption / release capacity, and have completed the present invention.

[0011] That is, the gist of the present invention is as follows. (1) An oxygen absorbing / releasing material containing a Rudolf Denne-Popper type layered perovskite complex oxide represented by the following formula (0): RE(Fe 1-a M a )3Sr3O 10-δ (0) (In the formula, RE is one or more selected from the group consisting of Pr, Nd, Sm, Eu, Gd, and La, M is one or more selected from the group consisting of Mn, Ni, and Co, a is a real number equal to or greater than 0 and less than 1, and δ is a real number equal to or greater than 0 and less than 1.) (2) An oxygen absorbing / releasing material containing a Rudolf Denne-Popper type layered perovskite complex oxide represented by the following formula (1): La(Fe 1-a M a )3Sr3O 10-δ (1) (In the formula, M is one or more selected from the group consisting of Mn, Ni, and Co, a is a real number of 0 or more and less than 1, and δ is a real number of 0 or more and less than 1.) (3) The oxygen storage / release material according to (1) or (2) above, wherein in the formulas (0) and (1), a is 0. (4) The oxygen storage / release material according to (1) or (2) above, wherein in the formulas (0) and (1), a is a real number greater than 0 and less than 1. (5) The oxygen storage / release material according to (1), (2) or (4) above, wherein in the formulas (0) and (1), a is a real number of 0.1 or more and 0.3 or less. (6) The oxygen storage / release material according to any one of (1), (3) to (5) above, wherein in the formula (0), RE is one or more selected from the group consisting of Pr, Nd, Eu and Gd. (7) A catalyst for purifying exhaust gas, comprising the oxygen absorbing material according to any one of (1) to (6) above and a precious metal supported on the oxygen absorbing material. Effect of the Invention

[0012] According to the present invention, it is possible to provide an oxygen absorbing / releasing material having improved low-temperature operability and oxygen absorbing / releasing capacity. [Brief description of the drawings]

[0013] [Figure 1A] FIG. 1 shows a schematic diagram of the composite oxide (RE(Fe1-aMa)3Sr3O10-δ) of the present invention having a Rudolfsden-Popper type layered perovskite crystal structure. [Figure 1B] 1 shows XRD patterns of Example 1, Comparative Example 1, and Comparative Example 2. [Figure 1C] The results of H2-TPR analysis of Example 1, Comparative Example 1, and Comparative Example 2 are shown. [Diagram 2]Figure 2A shows the XRD patterns of the new sample, the sample after H2 treatment, and the sample after reoxidation in Example 1. Figure 2B shows a schematic diagram of the transfer reaction between LaSr3Fe3O10-δ and LaSr3Fe3O9. Figure 2C shows the results of the XAFS analysis of the X-ray absorption spectrum of the new sample, the sample after H2 treatment, and the sample after reoxidation in Example 1. [Diagram 3] 1 shows XRD patterns of Examples 1 to 4. [Figure 4] 1 shows the results of H2-TPR analysis of Example 5, Comparative Example 3, and Comparative Example 4. [Diagram 5] 1 shows the results of H2-TPR analysis of Examples 5 to 8. [Figure 6] 1 shows XRD patterns of Examples 1, and 9 to 13. [Figure 7] 1 shows XRD patterns of Comparative Examples 7 to 13. [Figure 8] The results of H2-TPR analysis of Examples 1 and 9 to 13 are shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Preferred embodiments of the present invention will now be described in detail.

[0015] The oxygen absorbing / releasing material of the present invention contains a Rudolf Denne-Popper type layered perovskite complex oxide (hereinafter also referred to as the complex oxide of the present invention) represented by the following formula (0), and preferably consists of the complex oxide. RE(Fe 1-a M a )3Sr3O 10-δ (0) (In the formula, RE is one or more selected from the group consisting of praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), and lanthanum (La), M is one or more selected from the group consisting of manganese (Mn), nickel (Ni), and cobalt (Co), a is a real number equal to or greater than 0 and less than 1, and δ is a real number equal to or greater than 0 and less than 1.)

[0016] In the formula (0), RE is at least one selected from the group consisting of Pr, Nd, Sm, Eu, Gd and La, and preferably at least one selected from these. From the viewpoint of excellent oxygen absorbing and releasing ability at lower temperatures, RE is preferably at least one selected from the group consisting of Pr, Nd, Eu and Gd, and more preferably Pr, Nd, Eu or Gd.

[0017] In one embodiment, the oxygen-absorbing material of the present invention is one in which RE in formula (0) is La, and is represented by the following formula (1). La(Fe 1-a M a )3Sr3O 10-δ (1) (In the formula, M is one or more selected from the group consisting of manganese (Mn), nickel (Ni), and cobalt (Co), a is a real number that is equal to or greater than 0 and less than 1, and δ is a real number that is equal to or greater than 0 and less than 1.)

[0018] The composite oxide of the present invention can exhibit excellent oxygen absorbing and releasing capacity even at low temperatures without undergoing structural collapse even when exposed to a high-temperature reducing atmosphere. Therefore, the oxygen absorbing and releasing material containing the composite oxide of the present invention has high oxygen absorbing and releasing capacity and excellent low-temperature operability.

[0019] The complex oxide of the present invention has a Rudolfsden-Popper type layered perovskite crystal structure. Because the complex oxide of the present invention has this crystal structure, it is able to exhibit excellent oxygen absorption and release capacity without being destroyed even when exposed to a high-temperature reducing atmosphere. In the present invention, the crystal structure of the complex oxide can be determined, for example, by powder X-ray diffraction (XRD) measurement.

[0020] FIG. 1A shows the composite oxide (RE(Fe 1-a M a )3Sr3O 10-δ) is shown. Here, it is generally known that the oxidation number of Fe in an iron compound is 3 or 2, with 3 being the most stable oxidation number. In formula (0), δ is a real number equal to or greater than 0 and less than 1, so that, for example, when a is 0, the oxidation number of Fe is higher than 3. It is believed that the composite oxide of the present invention can exhibit high oxygen absorbing and releasing capacity because Fe has an abnormally high valence.

[0021] In one embodiment, in formulas (0) and (1), a is 0, that is, the composite oxide does not contain the metal element M.

[0022] In another embodiment, in the formulas (0) and (1), a is a real number greater than 0 and less than 1, that is, the composite oxide contains a metal element M. The composite oxide of the present invention further improves the oxygen absorbing and releasing capacity by containing one or more metal elements M selected from the group consisting of Mn, Ni, and Co. In the formulas (0) and (1), a is preferably a real number of 0.1 or more and 0.3 or less from the viewpoint of resource chemistry and cost.

[0023] In formulas (0) and (1), δ is a real number of 0 or more and less than 1, preferably a real number of 0 or more and 0.5 or less, and more preferably 0.25. As described above, it is believed that the composite oxide of the present invention can exhibit high oxygen absorption / release capacity because the oxidation number of Fe is abnormally high, that is, higher than 3.

[0024] The composite oxide of the present invention can be prepared, for example, by a complex polymerization method. In a preferred embodiment, the composite oxide of the present invention can be prepared, for example, by dissolving in water salts of each metal constituting the composite oxide, a carboxylic acid (preferably citric acid) and a glycol (preferably ethylene glycol) in a predetermined amount relative to the total amount of the metal salts to obtain a mixture thereof, heating and stirring the mixture at, for example, 70°C to 200°C to produce a gel, which is then pre-baked and then baked. In this embodiment, the temperature for the bake is usually 800°C to 1600°C, and preferably 1200°C to 1600°C.

[0025] The composite oxide of the present invention exhibits high oxygen absorbing and releasing capacity and can therefore be suitably used as an oxygen absorbing and releasing material.

[0026] The present invention also includes an exhaust gas purification catalyst using the oxygen absorbing / releasing material. The exhaust gas purification catalyst of the present invention contains the oxygen absorbing / releasing material and a precious metal (preferably a precious metal supported on the oxygen absorbing / releasing material). In another embodiment, the exhaust gas purification catalyst of the present invention does not need to contain a precious metal.

[0027] The noble metal that can be used in the exhaust gas purification catalyst of the present invention is not particularly limited and may be, for example, gold (Au), silver (Ag), platinum (Pt), palladium (Pd), rhodium (Rh), iridium (Ir), ruthenium (Ru) and osmium (Os), preferably Pt, Pd and Rh, more preferably Pd.

[0028] In the exhaust gas purifying catalyst of the present invention, the content of the noble metal is usually 0.001% by weight to 10% by weight, and preferably 0.01% by weight to 5% by weight, based on the oxygen absorbing / releasing material. EXAMPLES

[0029] The present invention will be described in more detail below with reference to examples, although the technical scope of the present invention is not limited to these examples.

[0030] <Synthesis of Complex Oxides> The composite oxides of the present invention were synthesized by a complex polymerization method. Specifically, each metal salt, citric acid and ethylene glycol (8.57 equivalents relative to the total amount of the metal salts) were dissolved in ion-exchanged water, and then the mixture was heated and stirred to produce a gel, which was then pre-baked and then main-baked to synthesize each composite oxide powder. The specific procedure is described below. Note that the number of moles of hydrates is the number of moles of anhydrous form.

[0031] Example 1: LaSrFeO 10-δ Citric acid (400 mmol) was added to a beaker and dissolved in ion-exchanged water (180 mL). Fe(NO3)3·9H2O (20 mmol), SrCO3 (20 mmol), and La(NO3)3·9H2O (6.67 mmol) were then added, followed by ethylene glycol (400 mmol) and stirring at room temperature for 30 minutes. After stirring, the mixture was aged at 130°C for 30 minutes to 1 hour to form a gel, which was then pre-baked at 350°C for 1 to 2 hours to give LaSr3Fe3O 10-δ The precursor powder was then sintered at 1400°C for 2 hours to synthesize the desired composite oxide.

[0032] Example 2: LaSr3(Fe 0.8 Mn 0.2 )3O 10-δ The target composite oxide was synthesized in the same manner as in Example 1, except that Fe(NO3)3·9H2O (20 mmol) was changed to Fe(NO3)3·9H2O (16 mmol) and Mn(NO3)2·6H2O (4 mmol).

[0033] Example 3: LaSr3(Fe 0.8 Co 0.2 )3O 10-δ The target composite oxide was synthesized in the same manner as in Example 1, except that Fe(NO3)3·9H2O (20 mmol) was changed to Fe(NO3)3·9H2O (16 mmol) and Co(NO3)2·6H2O (4 mmol).

[0034] Example 4: LaSr3(Fe 0.8 Ni 0.2 )3O 10-δ The target composite oxide was synthesized in the same manner as in Example 1, except that Fe(NO3)3·9H2O (20 mmol) was changed to Fe(NO3)3·9H2O (16 mmol) and Ni(NO3)2·6H2O (4 mmol).

[0035] Comparative example 1: Sr3Fe2O 7-δ Citric acid (400 mmol) was added to a beaker and dissolved in ion-exchanged water (180 mL). Fe(NO3)3·9H2O (13.3 mmol) and SrCO3 (20 mmol) were then added, followed by ethylene glycol (400 mmol) and stirring at room temperature for 30 minutes. After stirring, the mixture was aged at 130°C for 30 minutes to 1 hour to form a gel, which was then pre-baked at 350°C for 1 to 2 hours to give Sr3Fe2O 7-δ The precursor powder was then calcined at 1000°C for 5 hours to synthesize the desired composite oxide.

[0036] Comparative Example 2: SrFeO 3-δ Citric acid (400 mmol) was added to a beaker and dissolved in ion-exchanged water (180 mL). Fe(NO3)3·9H2O (20 mmol) and SrCO3 (20 mmol) were then added, followed by ethylene glycol (400 mmol) and stirring at room temperature for 30 minutes. After stirring, the mixture was aged at 130°C for 30 minutes to an hour to form a gel, which was then pre-baked in a mantle heater at 350°C for 1 to 2 hours to give SrFeO 3-δ The precursor powder was then calcined at 1000°C for 2 hours to synthesize the desired composite oxide.

[0037] <Analysis and performance evaluation> Powder X-ray Diffraction (XRD) The analysis was performed using a horizontal-sample multipurpose X-ray diffractometer (Miniflex and SmartLab Studio II, Rigaku Corp.) with Cu Kα [40 kV, 15 mA (Miniflex), 50 mA (SmartLab Studio II)] as the X-ray source.

[0038] Hydrogen Temperature Programmed Reduction (H2-TPR) A Belcat A manufactured by Microtrack Bell was used. Approximately 50 mg of sample powder was precisely weighed and introduced into the sample tube, then the sample was heated to 500°C while 20% O2 / He was passed through at 30 mL / min, pre-treated for 10 minutes, and then cooled. After replacing with Ar gas, 5% H2 / Ar was passed through at 30 mL / min, and the sample was heated at 10°C / min while being heated, and the hydrogen (H2) consumption was analyzed. The analysis was performed with a thermal conductivity detector (TCD), and a desiccant was placed in front of the TCD to trap the water produced.

[0039] X-ray absorption fine structure (XAFS) The measurements were performed using a fluorescence method at beamline BL01B1 of the SPring-8 large-scale synchrotron radiation facility of the Japan Synchrotron Radiation Research Institute, a public interest incorporated foundation.

[0040] Oxygen storage test by thermogravimetry The oxygen absorption / release capacity was measured using a thermogravimetric analyzer (TG STA 2500 Regulus, NETZSCH). 100 mg of sample (sized to 0.3 mm to 0.7 mm) was placed on a balance and held at 500°C for 1 hour under a 2% O2 / Ar flow. After that, the weight change was analyzed when 2% H2 / Ar (100 mL / min) and 2% O2 / Ar (100 mL / min) were flowed at 500°C while switching between them every 20 minutes, and the amount of oxygen absorbed and released was calculated.

[0041] Oxygen storage test using CO / O2 alternating pulse method Two grams of sample pellets were placed in a fixed-bed flow reactor, and the conversion behavior of each gas was examined using an FT-IR analyzer (Best Instruments SESAM-HL) and an oxygen meter (BEX). The sample was heated to 500°C while flowing 10% O2 / N2 gas at a flow rate of 10 L / min. At the same flow rate and temperature, 1% O2 / N2 and 2% CO / N2 were introduced sequentially for 6 cycles, each for 120 seconds, and the average value of the 2nd to 5th cycles of the amount of CO2 generated during the CO introduction period was calculated as the amount of oxygen absorbed and released.

[0042] <Analysis and performance evaluation of complex oxides> Figure 1B shows LaSrFeO 10-δ (Example 1) SrFeO7-δ (Comparative Example 1) and SrFeO 3-δ 1B shows the XRD pattern of Comparative Example 2. As shown in FIG. 1B, the diffraction lines of Comparative Example 2 matched the diffraction pattern characteristic of cubic perovskite. On the other hand, the diffraction lines of Example 1 and Comparative Example 1 each had the strongest line at about 32° split into two, matching the diffraction pattern characteristic of Rdolphin-Popper type layered perovskite.

[0043] LaSrFeO 10-δ (Example 1) SrFeO 7-δ (Comparative Example 1) and SrFeO 3-δ The reduction behavior of Fe ions in (Comparative Example 2) was evaluated by hydrogen temperature-programmed reduction (H2-TPR). 10-δ (Example 1) SrFeO 7-δ (Comparative Example 1) and SrFeO 3-δ The results of H2-TPR analysis of Comparative Example 2 are shown in FIG. 1C. The hydrogen consumption peak at 500° C. in Comparative Example 2 is expressed by the formula 1: SrFeO3+1 / 2H2→SrFeO 2.5 The hydrogen consumption observed at 700°C or higher in Comparative Example 2 is due to a topotactic transition reaction without the collapse of the oxide structure, as shown by the formula 2: 3SrFeO3+1 / 2H2→Sr3Fe2O6+Fe+1 / 2H2O. On the other hand, the hydrogen consumption observed at 700°C or higher in Comparative Example 2 is due to an irreversible reaction accompanied by the collapse of the oxide structure, as shown by the formula 2: 3SrFeO3+1 / 2H2→Sr3Fe2O6+Fe+1 / 2H2O. On the other hand, in Example 1 and Comparative Example 1, hydrogen consumption with main peaks at 490°C and 510°C, respectively, was detected, and both were attributed to hydrogen consumption due to topotactic transition. Unlike Comparative Example 2, in Example 1 and Comparative Example 1, hydrogen consumption due to the collapse of the oxide structure at 700°C or higher was hardly observed, indicating that the structural stability was increased compared to Comparative Example 2 due to the unique structure of the layered perovskite. In addition, the hydrogen consumption peak temperature was 490°C in Example 1, which was observed at a lower temperature than 510°C in Comparative Example 1, indicating that Example 1 exhibited oxygen desorption at a lower temperature than Comparative Example 1, and was superior in low-temperature operation.

[0044] LaSrFeO 10-δA sample (sample after H2 treatment) was prepared by treating (Example 1: new) with 2% H2 / Ar at 500°C to reduce it, and a sample (sample after reoxidation) was prepared by reoxidizing it with 2% O2 / Ar, and these were analyzed. Figure 2A shows the XRD patterns of the new sample of Example 1, the sample after H2 treatment, and the sample after reoxidation. In Figure 2A, the XRD pattern of the sample after H2 treatment matches the XRD pattern of LaSr3Fe3O9, which indicates that the oxide structure was not destroyed by the H2 treatment and the LaSr3Fe3O 10-δ The oxygen in the middle layer was inserted or removed, and the Fe coordination was transformed from 6 to 4. 10-δ The schematic diagram of the transfer reaction between LaSr3Fe3O9 and LaSr3Fe3O9 is shown. On the other hand, the XRD pattern of the reoxidized sample was completely consistent with that of the fresh sample, indicating that the topotactic adsorption and desorption of oxygen proceeds reversibly in this composite oxide.

[0045] FIG. 2C shows the results of XAFS analysis of the X-ray absorption spectrum of the new sample, the H2-treated sample, and the reoxidized sample of Example 1. As shown in FIG. 2C, in the structure near the X-ray absorption edge, the Fe K-absorption edge energy of the new sample of Example 1 roughly corresponds to a valence of 3.5. The absorption edge energy of the H2-treated sample shifted to the lower energy side, and it was reduced to trivalent Fe. By reoxidizing, the oxidation number of Fe was restored to 3.5, the same as that of the new sample. These results, like the XRD analysis results shown in FIG. 2A, indicate that the adsorption and desorption of oxygen in this composite oxide proceeds reversibly. Thus, LaSr3Fe3O 10-δ The oxidation number of Fe in Example 1 is an abnormally high valence, higher than 3, which is believed to contribute to the development of excellent oxygen absorbing and releasing capacity.

[0046] Figure 3 shows LaSrFeO 10-δ (Example 1) and LaSrFeO 10-δ3 shows the XRD patterns of Examples 2 to 4 in which Fe was partially substituted with Mn, Co, or Ni, respectively. As shown in Fig. 3, in Examples 2 to 4, as in Example 1, the diffraction lines were split into two at the strongest line near 32°, which matched the diffraction pattern characteristic of the Rdolphin-Popper type layered perovskite.

[0047] The results of the oxygen storage test by thermogravimetric analysis for the composite oxides of Examples 1 to 4 and Comparative Example 1 are shown in Table 1. As shown in Table 1, LaSr3Fe3O 10-δ (Example 1) shows Sr3Fe2O, which is capable of reversible topotactic transformation. 7-δ The composite oxides of Example 1 and Comparative Example 1 showed a larger amount of oxygen absorption and release than the composite oxide of Comparative Example 1. Both the composite oxides of Example 1 and Comparative Example 1 have an abnormally high valence of Fe, with the oxidation number being higher than 3, and are therefore considered to be able to exhibit high oxygen absorption and release capacity. The composite oxide of Example 1 has a larger Fe content per weight than the composite oxide of Comparative Example 1, which is presumably one of the reasons for the higher oxygen absorption and release capacity compared to the composite oxide of Comparative Example 1. Also, LaSr3Fe3O 10-δ The composite oxides of Examples 2 to 4, in which 20% of the Fe in Example 1 was replaced with Mn, Co or Ni, respectively, exhibited even greater oxygen absorption and release amounts than the composite oxide of Example 1.

[0048] [Table 1]

[0049] <Preparation of catalyst> Catalysts were prepared by supporting palladium on each of the composite oxides of Examples 1 to 4 and Comparative Examples 1 and 2 so that the amount of palladium was 1% by weight relative to the composite oxide. In addition, a catalyst was prepared using a ceria-zirconia composite oxide. The specific procedure is described below.

[0050] Catalysts of Examples 5 to 8 and Comparative Examples 3 and 4 Acetone was added to a beaker to dissolve palladium acetate. Each of the composite oxides of Examples 1 to 4 and Comparative Examples 1 and 2 was added thereto, and the mixture was heated and stirred to distill off the solvent. After drying overnight at 120°C, the resulting solid was crushed in a mortar and calcined at 500°C for 2 hours to prepare a catalyst. The catalysts prepared using each of the composite oxides of Examples 1 to 4 and Comparative Examples 1 and 2 were named Examples 5 to 8 and Comparative Examples 3 and 4, respectively.

[0051] Catalysts of Comparative Examples 5 and 6 Distilled water was added to a beaker, and palladium nitrate was dissolved therein. A commercially available ceria-zirconia composite oxide was added thereto, and the mixture was heated and stirred to remove the solvent. After drying overnight at 120°C, the resulting solid was crushed in a mortar and calcined at 500°C for 2 hours to prepare a catalyst. As the ceria-zirconia composite oxide, composite oxides of CeO2 / ZrO2=67 / 33 and CeO2 / ZrO2=33 / 67 were used, and the catalysts prepared using these were designated Comparative Examples 5 and 6, respectively.

[0052] <Catalyst analysis and performance evaluation> Figure 4 shows the Pd / LaSr3Fe3O 10-δ (Example 5) Pd / SrFeO 7-δ (Comparative Example 3) and Pd / SrFeO 3-δ 4 shows the results of H2-TPR analysis of Comparative Example 4. In FIG. 4, hydrogen consumption attributable to the topotactic transition with a peak at 85° C. was observed in Comparative Example 4, and the SrFeO 3-δAs in Comparative Example 2, hydrogen consumption due to the collapse of the oxide structure was detected at 700°C or higher. On the other hand, in Example 5 and Comparative Example 3, hydrogen consumption attributable to the topotactic transition was observed at 83°C and 98°C, respectively, but hydrogen consumption due to the collapse of the oxide structure at 700°C or higher was hardly observed. These results showed that catalysts carrying precious metals such as palladium also have high structural stability of the Rudolfsden-Popper type layered perovskite. In addition, the hydrogen consumption peak temperature (83°C) in Example 5 was observed at a lower temperature than that in Comparative Example 3 (98°C), indicating that oxygen desorption occurs at a lower temperature in Example 5 and that it is superior in low-temperature operation. Thus, LaSr3Fe3O 10-δ (Example 1) and Pd / LaSrFeO 10-δ All of the catalysts (Example 5) exhibited excellent low-temperature operability in comparison with conventional composite oxides and catalysts using the same (Comparative Examples 1 and 3), which are known to have high structural stability in a reducing atmosphere and high oxygen absorption / release capacity.

[0053] Figure 5 shows the Pd / LaSr3Fe3O 10-δ (Example 5) and LaSrFeO 10-δ 5 shows the results of H2-TPR analysis of catalysts (Examples 6 to 8) using composite oxides in which Fe in LaSr3Fe3O is partially substituted with Mn, Co, or Ni, respectively. As shown in FIG. 5, in all of Examples 5 to 8, hydrogen consumption attributable to topotactic transition was observed near 100°C, and hydrogen consumption due to the collapse of the oxide structure at 700°C or higher was hardly observed. These results are consistent with those of LaSr3Fe3O 10-δ Catalysts using composite oxides in which part of the Fe in the catalyst is replaced by Mn, Co, or Ni, respectively, also showed high structural stability of the Rdolphin-Popper type layered perovskite.

[0054] The catalysts of Examples 5 to 8 and Comparative Examples 3, 5, and 6 were subjected to an oxygen storage test by the CO / O2 alternating pulse method. The results are shown in Table 2. As shown in Table 2, Pd / LaSr3Fe3O 10-δIn Example 5, a catalyst in which Pd is supported on a conventional iron-based composite oxide capable of reversible topotactic transition, Pd / SrFeO 7-δ (Comparative Example 3), and a catalyst in which Pd is supported on a conventional ceria-zirconia composite oxide known to have high oxygen adsorption and desorption capacity, Pd / Ce 0.7 Zr 0.3 O2 (comparative example 5), Pd / Ce 0.3 Zr 0.7 The amount of oxygen absorbed and released was larger than that of Pd / LaSr3Fe3O2 (Comparative Example 6), demonstrating excellent oxygen absorption and release capacity. 10-δ The catalysts of Examples 6 to 8, in which 20% of the Fe in the composite oxide of Example 5 was replaced with Mn, Co or Ni, respectively, had a larger oxygen absorption / release amount than the catalyst of Example 5 and showed a higher oxygen absorption / release capacity.

[0055] [Table 2]

[0056] <Synthesis of Complex Oxides 2> The composite oxide of Example 1 (LaSrFeO 10-δ In the above, La was replaced with another metal to produce composite oxides of Examples 9 to 13 and Comparative Examples 7 to 13. Note that the number of moles given for hydrates is the number of moles for the anhydride.

[0057] Example 9: PrSrFeO 10-δ The target composite oxide was synthesized in the same manner as in Example 1, except that La(NO3)3·9H2O (6.67 mmol) was changed to Pr(NO3)3·6H2O (6.67 mmol).

[0058] Example 10: NdSrFeO 10-δ The target composite oxide was synthesized in the same manner as in Example 1, except that La(NO3)3·9H2O (6.67 mmol) was changed to Nd(NO3)3·6H2O (6.67 mmol).

[0059] Example 11: SmSrFeO10-δ The target composite oxide was synthesized in the same manner as in Example 1, except that La(NO3)3·9H2O (6.67 mmol) was changed to Sm(NO3)3·6H2O (6.67 mmol).

[0060] Example 12: EuSrFeO 10-δ The target composite oxide was synthesized in the same manner as in Example 1, except that La(NO3)3·9H2O (6.67 mmol) was changed to Eu(NO3)3·6H2O (6.67 mmol).

[0061] Example 13: GdSrFeO 10-δ The target composite oxide was synthesized in the same manner as in Example 1, except that La(NO3)3·9H2O (6.67 mmol) was changed to Gd(NO3)3·5H2O (6.67 mmol).

[0062] Comparative Example 7: YSrFeO 10-δ The target composite oxide was synthesized in the same manner as in Example 1, except that La(NO3)3·9H2O (6.67 mmol) was changed to Y(NO3)3·6H2O (6.67 mmol).

[0063] Comparative Example 8: CeSrFeO 10-δ The target composite oxide was synthesized in the same manner as in Example 1, except that La(NO3)3·9H2O (6.67 mmol) was changed to Ce(NO3)3·6H2O (6.67 mmol).

[0064] Comparative Example 9: TbSrFeO 10-δ The target composite oxide was synthesized in the same manner as in Example 1, except that La(NO3)3·9H2O (6.67 mmol) was changed to Tb(NO3)3·5H2O (6.67 mmol).

[0065] Comparative Example 10: DySrFeO 10-δ The target composite oxide was synthesized in the same manner as in Example 1, except that La(NO3)3·9H2O (6.67 mmol) was changed to Dy(NO3)3·5H2O (6.67 mmol).

[0066] Comparative Example 11: HoSrFeO 10-δ The target composite oxide was synthesized in the same manner as in Example 1, except that La(NO3)3·9H2O (6.67 mmol) was changed to Ho(NO3)3·5H2O (6.67 mmol).

[0067] Comparative Example 12: ErSrFeO 10-δ The target composite oxide was synthesized in the same manner as in Example 1, except that La(NO3)3·9H2O (6.67 mmol) was changed to Er(NO3)3·5H2O (6.67 mmol).

[0068] Comparative Example 13: YbSrFeO 10-δ The target composite oxide was synthesized in the same manner as in Example 1, except that La(NO3)3·9H2O (6.67 mmol) was changed to Yb(NO3)3·5H2O (6.67 mmol).

[0069] FIG. 6 shows the XRD patterns of Examples 1 and 9 to 13. FIG. 7 shows the XRD patterns of Comparative Examples 7 to 13. As shown in FIG. 6, the diffraction lines of Examples 9 to 13, like those of Example 1, have the strongest line at about 32° split into two, and are consistent with the diffraction pattern characteristic of the Rudolf-Popper type layered perovskite. On the other hand, as shown in FIG. 7, in Comparative Examples 7 to 13, the diffraction lines of SrFeO3 and (RE)2O3 (RE is Y, Ce, Tb, Dy, Ho, Er, or Yb, respectively) are detected, and it is recognized that the Rudolf-Popper type layered perovskite was not generated.

[0070] FIG. 8 shows the results of H2-TPR analysis of Examples 1 and 9 to 13. As described above with respect to FIG. 1C, in Example 1, a hydrogen consumption peak was detected at 490°C, which was attributed to hydrogen consumption due to topotactic transition. As described above, in Example 1, hydrogen consumption due to the collapse of the oxide structure at 700°C or higher was hardly observed, and structural stability was improved. In addition, oxygen desorption occurred from a low temperature of 490°C, and low-temperature operability was excellent. As shown in FIG. 8, the hydrogen consumption peaks of Examples 9 to 13 were observed at a low temperature equal to or lower than that of Example 1, indicating that oxygen desorption occurred from a low temperature equal to or lower than that of Example 1. In addition, in Examples 9 to 13, hydrogen consumption was hardly observed at 600°C or higher, which indicated that structural collapse due to reduction to zero-valent metal hardly occurred.

Claims

1. An oxygen absorbing / releasing material comprising a Rudolfsden-Popper type layered perovskite complex oxide represented by the following formula (0): RE(Fe 1-a M a ) 3 Sr 3 O 10-δ (0) (In the formula, RE is one or more selected from the group consisting of Pr, Nd, Sm, Eu, Gd, and La, M is one or more selected from the group consisting of Mn, Ni, and Co, a is a real number equal to or greater than 0 and less than 1, and δ is a real number equal to or greater than 0 and less than 1.)

2. An oxygen absorbing / releasing material comprising a Rudolfsden-Popper type layered perovskite complex oxide represented by the following formula (1): La(Fe 1-a M a ) 3 Sr 3 O 10-δ (1) (In the formula, M is one or more selected from the group consisting of Mn, Ni, and Co, a is a real number equal to or greater than 0 and less than 1, and δ is a real number equal to or greater than 0 and less than 1.)

3. 3. The oxygen storage / release material according to claim 1, wherein a is 0 in the formulas (0) and (1).

4. 3. The oxygen storage / release material according to claim 1, wherein in the formulas (0) and (1), a is a real number greater than 0 and less than 1.

5. 5. The oxygen storage / release material according to claim 4, wherein in the formulas (0) and (1), a is a real number of 0.1 or more and 0.3 or less.

6. 2. The oxygen storage / release material according to claim 1, wherein in said formula (0), RE is at least one selected from the group consisting of Pr, Nd, Eu and Gd.

7. 3. An exhaust gas purifying catalyst comprising the oxygen absorbing material according to claim 1 or 2 and a precious metal supported on the oxygen absorbing material.

Citation Information

Patent Citations

  • Iron oxide-zirconia composite oxide and method for producing the same

    JP2013241328A